2013
DOI: 10.1260/1475-472x.12.7-8.679
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Jet Noise Reduction by Chevrons and Fluidic Injection

Abstract: This work focuses on the noise reduction capabilities of chevrons, fluidic injection, and a combination of both. The control mechanisms were experimentally investigated for over, under, and ideally expanded operating conditions. Acoustic far-field data was collected to quantify noise reductions and changes to the flow field through use of theoretical relations. Results show appreciable noise reduction by both fluidic injection and chevrons. Optimal performance of the two technologies occured at opposite ends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This concept evolved into the modern chevron design, which has been the topic of many more recent studies. [130][131][132][133][134][135][136][137][138] While chevron technology has offered a sufficiently attractive trade-off between noise and thrust to justify their inclusion on a number of modern engines, a full phenomenological explanation of the mechanism by which they achieve this trade-off is yet lacking. From the perspective of screech, however, it seems likely that chevrons suppress resonance in much the same manner as tabs and notches: some combination of reduced hydrodynamic growth rates, reduced shock strength and reduced receptivity.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…This concept evolved into the modern chevron design, which has been the topic of many more recent studies. [130][131][132][133][134][135][136][137][138] While chevron technology has offered a sufficiently attractive trade-off between noise and thrust to justify their inclusion on a number of modern engines, a full phenomenological explanation of the mechanism by which they achieve this trade-off is yet lacking. From the perspective of screech, however, it seems likely that chevrons suppress resonance in much the same manner as tabs and notches: some combination of reduced hydrodynamic growth rates, reduced shock strength and reduced receptivity.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…The injection of water at the inflow point does not directly produce sound at the input point since it is a steady injection. However, injection in general (gas or water) adds momentum that, in principle, can increase sound, but as in various gas injection cases such as that of Heeb et al 52 and Sinha et al, 53 it is believed that the momentum addition/exchange results in reducing the noise-producing large-scale structure in the jet. Similar effects of water injection are also pointed out by Kandula.…”
Section: Effect Of Water On the Flow Perturbationsmentioning
confidence: 99%
“…Brenda Henderson shows that the water jet reduces the total sound pressure level by about 6 dB, and the gas jet can reduce the total sound pressure level by about 2 dB [4]. N. Heeb's experiments have shown that hydrodynamic noise can be reduced by both jet injection and serrated construction [5]. Yiping Wang found that the upstream concave surface can effectively suppress the cavity flow oscillation [6].…”
Section: Introductionmentioning
confidence: 99%